2014
DOI: 10.1158/0008-5472.can-13-1349
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Immunoregulatory CD271+ Cells by Metastatic Tumor Cells That Express Human Endogenous Retrovirus H

Abstract: Human endogenous retroviruses (HERV) are associated with many diseases such as autoimmune diseases and cancer. Although the frequent expression of a variety of HERVs in tumor cells has been demonstrated, their functional contributions in cancer are as yet unclear. Intriguingly, HERVs and other retroviruses include an immunosuppressive domain in their transmembrane envelope proteins, but its mechanism of action and cancer relevance are obscure. In this study, we demonstrate that the human endogenous retrovirus … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 33 publications
0
48
1
Order By: Relevance
“…In another study, HERV-H was reported to be expressed in 2 of 12 PCs, with little expression in some normal tissues (63). However, HERV-H was expressed in normal pancreas tissue (64). …”
Section: Discussionmentioning
confidence: 99%
“…In another study, HERV-H was reported to be expressed in 2 of 12 PCs, with little expression in some normal tissues (63). However, HERV-H was expressed in normal pancreas tissue (64). …”
Section: Discussionmentioning
confidence: 99%
“…Infection of murine ERV‐env expression vector presenting the envelope immunosuppressive domain into cancer cells promoted tumor growth in vivo by preventing the activity of innate immune system that clears tumors . The immunosuppressive peptide H17, deriving from HERV‐H, was recently identified to induce epithelial‐mesenchymal transition and stimulate expression of the chemokine CCL19 in tumor cells …”
Section: Functional Roles Of Hervs In Carcinogenesismentioning
confidence: 99%
“…131 The immunosuppressive peptide H17, deriving from HERV-H, was recently identified to induce epithelial-mesenchymal transition and stimulate expression of the chemokine CCL19 in tumor cells. 132 In recent years, epigenetic therapies are under active investigation in diverse solid tumors, inducing immune responses and reactivating silenced tumor suppressors. 133,134 It has been shown that low doses of DNA methylation inhibitors 5-aza-2′-deoxycytidine (decitabine) or CDK4/6 inhibitors can induce the transcription of HERV-derived double-stranded RNAs (dsRNAs) and IFN-response genes in tumor cells.…”
Section: Regulation Of Innate Immunity By Hervsmentioning
confidence: 99%
“…Several studies over the last three decades have provided evidence to suggest that the envelope glycoprotein of certain retroviruses is immunosuppressive in vitro and in vivo (Cianciolo et al, 1985; de Parseval et al, 2001; Denner, 2014; Dupressoir et al, 2012; Haraguchi et al, 1997; Kudo-Saito et al, 2014; Mangeney et al, 2007; Schlecht-Louf et al, 2010). Although the precise molecular mechanism remains unresolved, immunosuppressive activity has been pinpointed at a short region of the transmembrane polypeptide that, together with the surface unit (SU), constitutes one part of the trimeric envelope glycoprotein (Cianciolo et al, 1985; Dupressoir et al, 2012; Schlecht-Louf et al, 2010).…”
Section: Introductionmentioning
confidence: 99%